The Idea of History in the Ancient Near East - Cameron, George G.
Ancient Persia: 1. Prologue — 2. The Setting — 3. “Father” Cyrus and History Rewritten — 4. “Huckster” Darius and History Remade — 5. Return to Old Ideas.